The Effect of Accounting Understanding and Financial Literacy on Student Financial Management with Lifestyle as a Mediating Variable - Okta Sulviana; Mukhzarudfa; Eko Prasetyo (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to analyze the influence of accounting understanding and financial literacy on student financial management, with lifestyle as a mediating variable. The subjects were active students of the Accounting Study Program, Faculty of Economics and Business, University of Jambi, graduating in the 2018–2021 intake, with 78 respondents. The research method used was quantitative, with data collection through questionnaires. Data analysis was performed using Partial Least Squares (PLS) with the assistance of SmartPLS 4 software. The results showed that accounting understanding had a positive and significant effect on student financial management. Financial literacy also had a positive and significant effect on student financial management. Furthermore, lifestyle was shown to mediate the effect of financial literacy on student financial management, but not the effect of accounting understanding on student financial management.